Pengaruh Price Discount dan in-Store Display terhadap Impulse Buying pada Matahari Department Store di Samarinda - Melina Melina; M. Amin Kadafi (Faculty of Economics and Business Mulawarman University, 2017)
The effect of Price Discount and In-Store Display toward Impulse Buying in Matahari Department Store Samarinda, under supervised by Mr. Suharno and Mr. M.Amin Kadafi. The purpose of this study is to know is there any positive influence and significant from price discount variable and In-store display toward impulse buying variable. The analysis technique employed in this research was the multiple linier regression analysis.Based on the result of the research and discussion of the data, the writer can conclude that price discount has positive effect and significant toward impulse buying in Matahari Department Store Samarinda.